Commonfund ESG - Elias, Jaan; Goetzmann, William N. ([London] : SAGE, 2016)
ESG (Environmental Social and Governance) investing had become an increasingly hot topic in the financial community. Could Commonfund offer its endowment clients some investment vehicle that would satisfy ESG concerns while producing sufficient returns?
Originally Published in: Elias, J., & Goetzmann, W. (2015). Commonfund ESG. 15-016. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/commonfund-esg.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Investments -- Moral and ethical aspects -- Case studies; Social responsibility of business -- Case studies; Nonprofit organizations -- Finance -- Case studies